Notas sobre el corpuscularismo, la causalidad y el movimiento en el Timeo de Platón - Manzo, Silvia (1998)
Timaeus's explanation of changes in nature uses simultaneously mechanical, animistic and teleological conceptions of motion. The geometrical model applied to the four elements determines mechanical motions in the cycle of transmutations. Attractive causality is postulated for explaining the union of the elements with the greater mass of their connaturals. The concentration of the elements inside of the sphere of the world, is derived from the final cause tending to the best. I try to show that such combination of different causalities implies theoretical inconsistencies, which can only be justified by the co-existence of the metaphysical principles of Intelligence and Necessity in the Timeic physics.